Пусть
![t = cosx t = cosx](https://tex.z-dn.net/?f=t+%3D+cosx)
, t ∈ [-1; 1].
Обратная замена:
x = ±
![\frac{ \pi }{3} + 2 \pi n \frac{ \pi }{3} + 2 \pi n](https://tex.z-dn.net/?f=+%5Cfrac%7B+%5Cpi+%7D%7B3%7D+%2B+2+%5Cpi+n)
, n ∈ Z
![x = \pi + 2\pi n x = \pi + 2\pi n](https://tex.z-dn.net/?f=x+%3D++%5Cpi++%2B+2%5Cpi+n)
, n ∈ Z.
При x ∈ [3π; 4π]
3π ≤±
![\frac{ \pi }{3} + 2 \pi n \frac{ \pi }{3} + 2 \pi n](https://tex.z-dn.net/?f=+%5Cfrac%7B+%5Cpi+%7D%7B3%7D++%2B+2+%5Cpi+n)
≤ 4π (умножим на 3 и разделим на π)
9 ≤ ±1 + 6n ≤ 12
При n ∈ Z, n = 2. Тогда x =
Теперь найдем корни для второго уравнения:
3π ≤ π + 2πn ≤ 4π (разделим на π)
3 ≤ 1 + 2n ≤ 4
2 ≤ 2n ≤ 3
При n ∈ Z n = 1.
Тогда
Ответ: